Not just pain and morning stiffness duration in the daily experience of patients with polymyalgia rheumatica. Does the rheumatologist listen to all patient-reported outcomes? - Ciro Manzo (Termedia Publishing House, 2021)
Patient-reported outcomes (PROs) provide a means for patients to communicate with their care teams about their disease. Polymyalgia rheumatica (PMR) is considered to be one of the most common inflammatory rheumatic diseases in older adults. The Visual Analogue Scale (VAS) of pain is the only PRO assessed by the PMR activity score (PMR-AS), which is still the only validated score for monitoring disease activity in patients affected with PMR. Other PROs such as fatigue, sleep disturbances, depressive symptoms, and patient’s perspective related to adverse effects of prednisolone are still unmet needs. This short communication suggests the gerontorheumatological outpatient clinic as an answer.